On the Question of the Need for a Built‐In Potential in Perovskite Solar Cells - Oskar Sandberg (Advanced Materials Interfaces, 2020)
Perovskite semiconductors as the active materials in efficient solar cells exhibit free carrier diffusion lengths on the order of microns at low illumination fluxes and many hundreds of nanometers under 1 sun conditions. These lengthscales are significantly larger than typical junction thicknesses, and thus the carrier transport and charge collection should be expected to be diffusion controlled. A consensus along these lines is emerging in the field. However, the question as to whether the built-in potential plays any role is still of matter of some conjecture. This important question using phase-sensitive photocurrent measurements and theoretical device simulations based upon the drift-diffusion framework is addressed. In particular, the role of the built-in electric field and charge-selective transport layers in state-of-the-art p–i–n perovskite solar cells comparing experimental findings and simulation predictions is probed. It is found that while charge collection in the junction does not require a drift field per se, a built-in potential is still needed to avoid the formation of reverse electric fields inside the active layer, and to ensure efficient extraction through the charge transport layers.